2021
DOI: 10.3389/fcvm.2021.669301
|View full text |Cite
|
Sign up to set email alerts
|

Left Bundle Branch Area Pacing vs. Biventricular Pacing for Cardiac Resynchronization Therapy: A Meta-Analysis

Abstract: Background: Left bundle branch area pacing (LBBAP) is a recently proposed method for conduction system pacing. We performed a meta-analysis of controlled studies to compare the clinical outcome in patients who received LBBAP vs. biventricular pacing (BVP) for cardiac resynchronization therapy (CRT).Methods: PubMed, Embase, and Cochrane's Library databases were searched for relevant controlled studies. A random-effect model incorporating the potential heterogeneity was used to synthesize the results.Results: Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…LBBaP is a physiological pacing method, and the efficacy of LBBaP is not inferior to that of BIV-CRT for heart failure with cardiac electromechanical activity asynchrony [2][3][4][5] . However, studies have shown that LBBaP cannot achieve cardiac resynchronization in patients with the following situations: (1) complete LBBB block sites distal to the LBB [8] , (2) nonspecific IVCD [6] , (3) myocardial fibrosis because of myocardial infarction or myocardiopathy [9] , (4) right atrium or right ventricle enlargement [9] , and (5) a tendency for interventricular septal perforation because of a thin or soft interventricular septum [10] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LBBaP is a physiological pacing method, and the efficacy of LBBaP is not inferior to that of BIV-CRT for heart failure with cardiac electromechanical activity asynchrony [2][3][4][5] . However, studies have shown that LBBaP cannot achieve cardiac resynchronization in patients with the following situations: (1) complete LBBB block sites distal to the LBB [8] , (2) nonspecific IVCD [6] , (3) myocardial fibrosis because of myocardial infarction or myocardiopathy [9] , (4) right atrium or right ventricle enlargement [9] , and (5) a tendency for interventricular septal perforation because of a thin or soft interventricular septum [10] .…”
Section: Discussionmentioning
confidence: 99%
“…The guideline recommends biventricular-CRT (BIV-CRT) as the primary method for the treatment of cardiac electromechanical dyssynchrony [1] . In recent years, increasing evidence has shown that the efficacy of left bundle branch area pacing (LBBaP) is not inferior to that of BIV-CRT for heart failure cardiac electromechanical activity asynchrony [2][3][4][5] . However, LBBaP is not suitable for all heart failure patients with cardiac desynchronization, and our center has treated such a patient.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, HBP and LBBP delivered similar improvement in the LVEF and NYHA class after the 1-year follow-up, which was significantly higher than that in BVP. Furthermore, some meta-analyses of LBBAP for CRT have been reported ( 62 , 63 ). A meta-analysis compared LBBAP and BVP for CRT ( 62 ).…”
Section: Left Bundle Branch Area Pacing For Cardiac Resynchronization...mentioning
confidence: 99%
“…Furthermore, some meta-analyses of LBBAP for CRT have been reported ( 62 , 63 ). A meta-analysis compared LBBAP and BVP for CRT ( 62 ). Compared with BVP, LBBAP produced significantly narrower QRSd with a mean difference (MD) 29.18 ms, LVEF improvement of 6.93%, LVEDD reduction of 2.96 mm, and NYHA class improvement of 0.54.…”
Section: Left Bundle Branch Area Pacing For Cardiac Resynchronization...mentioning
confidence: 99%
“…It is encouraging that a novel physiological pacing strategy, LBBaP that has emerged in recent years has significant advantages ( 18 ) ( Figures 1C , F ). Meanwhile, mounting evidence indicates that LBBaP appears to be an effective method for CRT, and is associated with improvements of symptoms and cardiac function ( 19 22 ). The result of latest, prospective, randomized study of LBBaP-CRT vs. BiV-CRT has shown that LBBaP-CRT could achieve better LVEF improvement than BiV-CRT in heart failure patients with non-ischemic cardiomyopathy and left bundle branch block (LBBB) ( 23 ).…”
Section: Introductionmentioning
confidence: 99%